2009
DOI: 10.1177/070674370905400108
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ziprasidone and Risperidone in the Long-Term Treatment of Schizophrenia: A 44-Week, Double-Blind, Continuation Study

Abstract: W La Revue canadienne de psychiatrie, vol 54, no 1, janvier 2009 46Objective: This randomized, double-blind, multicentre extension study compared the efficacy, tolerability, and safety of ziprasidone and risperidone for schizophrenia or schizoaffective disorder. Methods:Patients who had responded to treatment for an acute exacerbation of illness in an 8-week study received ziprasidone, 80 to 160 mg/day (n = 62), or risperidone, 6 to 10 mg/day (n = 77), for up to 44 additional weeks. Primary efficacy variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
0
18
0
2
Order By: Relevance
“…The results of both the acute and long-term treatment documented similar effi cacy and a diff erential pattern of side eff ects in both treatment arms. This is widely in concert with previous comparisons of ziprasidone and risperidone in monotherapy [2,16] , switch studies between the two antipsychotics [18,36,37] as well as one recent long-term comparison over a period of 44 weeks [1] . As for the mode of action on psychotic symptoms and mood, we assume pharmacodynamic eff ects via receptors of several neurotransmitter systems.…”
Section: Discussion ▼mentioning
confidence: 80%
“…The results of both the acute and long-term treatment documented similar effi cacy and a diff erential pattern of side eff ects in both treatment arms. This is widely in concert with previous comparisons of ziprasidone and risperidone in monotherapy [2,16] , switch studies between the two antipsychotics [18,36,37] as well as one recent long-term comparison over a period of 44 weeks [1] . As for the mode of action on psychotic symptoms and mood, we assume pharmacodynamic eff ects via receptors of several neurotransmitter systems.…”
Section: Discussion ▼mentioning
confidence: 80%
“…Most reports indicate a low incidence of PRL elevation and low to moderate levels of HPRL with ziprasidone use [11, 15, 103, 234, 240, 245, 297, 324326]. Several studies found decreased PRL levels after, respectively, 6 weeks [301], 4–8 weeks [90], 18 weeks [327], 44 weeks [328] and 1 year [329] of treatment with ziprasidone. However, ziprasidone can also be associated with HPRL.…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
“…Los efectos de diferentes AP de segunda generación fueron comparados entre ellos en 5 meta análisis 20-24 y 1 experimento clínico 25 . En la tabla 5 se presenta el resumen de la Tabla 3 -Resumen de la evidencia de riesgo de hospitalización en las comparaciones entre AP de primera generación con los de segunda generación para el tratamiento de mantenimiento de la esquizofrenia Tabla 4 -Resumen de la evidencia de falla en el tratamiento en las comparaciones entre AP de primera generación con los de segunda generación para el tratamiento de mantenimiento de la esquizofrenia evidencia y la calidadde los desenlaces con información para estas comparaciones.…”
Section: Comparación Entre Ap De Segunda Generaciónunclassified
“…El único de los estudios incluidos que evaluó la evolución de los síntomas negativos durante el manejo en fase de mantenimiento fue el experimento conducido por Addington y colaboradores 25 . Se observa una diferencia estadísticamente significativa en la disminución de los síntomas con el uso de ziprasidona comparada con risperidona utilizando la subescala de síntomas negativos de la escala PANSS, pero con limitada importancia clínica (DM: −2.2 (IC 95% −1,67; −2,72)).…”
Section: Síntomas Negativosunclassified